ELECTRICAL AND HEAT SUPPLY OF THE OBJECT BY MEANS OF INNOVATIVE MEANS - WIND-SOLAR STATION (BCC) OF MEDIUM POWER AND ELECTRIC ENERGY SOURCE - Zh. Kambarov,; M.Zh. Tursunov,; M.S. Zhakupova,; S.I. Oleinik, (Academic Journal of Physical and Chemical Sciences, 2019)
Over the past decade, interest in renewable energy has been steadily increasing since it is practically unlimited. As fuel supplies become less reliable and more expensive, these sources become more attractive and more economical. The increase in oil and gas prices was the main reason that people again turned their attention to water, wind and the Sun. Interest in the problem of using solar energy has increased dramatically. The potentialities of energy based on the use of direct solar radiation are extremely high. Regardless of whether we use renewable energy or not, this will not affect the Earth’s energy balance and the state of the biosphere.